Implementasi Metode Laerning By Doing Dalam Meningkatkan Aktivitas Belajar Siswa Dalam Pembelajaran PAI di SMAN 3 Kota Bima - Ditya Fajrianti; Syafruddin Syafruddin; Kaharuddin Kaharuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the implementation of the learning-by-doing method in Islamic Religious Education (PAI) learning, as well as the supporting and inhibiting factors in enhancing students’ learning activities at SMAN 3 Kota Bima. This study employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that the implementation of the learning-by-doing method was carried out through worship practices, such as ablution and tayammum; simulations of funeral rites using mannequins; and role-playing activities in moral education materials. This method was effective in increasing students’ participation, enthusiasm, and self-confidence. The supporting factors included the principal’s policies, teachers’ creativity, school facilities, and students’ enthusiasm. Meanwhile, the inhibiting factors included limited learning time, differences in students’ prior abilities, limited interactive learning media, large class sizes, and the dynamics of curriculum changes.